THE COLLABORATION OF INTERCULTURAL EDUPRENEURS’ PROJECT-BASED LEARNING OF TEACHING ENGLISH FOR YOUNG LEARNERS IN BENGKULU PROVINCE - Parli, Muhammad; Angraini, Ria; Susyla, Dian; Safitri, Washlurachim (Universitas Muhammadiyah Makassar, 2025)
This study aimed to describe the collaboration of intercultural edupreneurs’ project-based learning (PjBL) of English for young learners in Bengkulu province. This descriptive qualitative study used observation, interview, and documentation to collect the primary data. The research samples involved five private English courses for young learners as a collaboration of intercultural edupreneurs’ project-based learning (PjBL) that was created by students of the student exchange (PMM) program and English students of Universitas Muhammadiyah Bengkulu. They were B 3nglish, Artery_ECourse, BVJE_Course, OBFiG’s_E Course, and BC.Equal Courses. The research results revealed that the collaboration of intercultural edupreneurs’ project-based learning (PjBL) of English for young learners in Bengkulu province was realized in four dimensions: planning and group decision-making; communicating about thinking; contributing resources, ideas, and efforts; and monitoring processes. In concluding the research, the collaboration of intercultural edupreneurs’ project-based learning (PjBL) of English for young learners is highly facilitated through the project-based learning method, making it an effective approach.